2019
DOI: 10.1128/mcb.00374-18
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Progression Regulates Biogenesis and Cellular Localization of Lipid Droplets

Abstract: Intracellular lipid accumulation has been associated with a poor prognosis in cancer. We have previously reported the involvement of lipid droplets in cell proliferation in colon cancer cells, suggesting a role for these organelles in cancer development. In this study, we evaluate the role of lipid droplets in cell cycle regulation and cellular transformation. Cell cycle synchronization of NIH 3T3 cells revealed increased numbers and dispersed distribution of lipid droplets specifically during S phase. Also, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 74 publications
(82 reference statements)
1
32
0
1
Order By: Relevance
“…In the present work, our results indicated that malignant breast cancer cells can diminish the TNBC MDA-MB-231 ability to proliferate by decreasing the expression of the LD structural protein ADRP. Cancer aggressiveness is also related to higher LD content in other tumor cells [9,44,45,46,47,48,49] and has been associated with cell invasiveness, and higher resistance to chemotherapy [50,51]. One plausible explanation is that LD can be used as energy substrates for further cellular proliferation, consequently increasing disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, our results indicated that malignant breast cancer cells can diminish the TNBC MDA-MB-231 ability to proliferate by decreasing the expression of the LD structural protein ADRP. Cancer aggressiveness is also related to higher LD content in other tumor cells [9,44,45,46,47,48,49] and has been associated with cell invasiveness, and higher resistance to chemotherapy [50,51]. One plausible explanation is that LD can be used as energy substrates for further cellular proliferation, consequently increasing disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…These organelles play a key role in harmonizing lipid trafficking for different cellular activities, especially providing a substrate for beta-oxidation and membrane synthesis [5]. An increase in cytoplasmic LD number in cancer cells is associated with higher aggressiveness and poor prognostic in several types of cancer such as breast cancer [6,7], colon cancer [8,9] and prostate cancer [10]. In a process known as lipophagy, where the degradation of stored lipids occurs, fatty acids can be mobilized from LD [11] and fuel cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a growing body of evidence suggest that enhanced LD amount may cope a wide range of stressful cellular conditions, by modulating lipid metabolism, providing this macromolecule for structural and energetics needs, as well as for inflammatory mediators production, enabling cancer cell survival and tumor growth 54 . In this sense, our group has recently demonstrated that cellular proliferation is based on LD meticulous regulation, pointing out an important link between cell cycle progression, cell proliferation and lipid accumulation 55 . Furthermore, lipid metabolism has been recognized as crucial for supporting cell proliferation 56 , through distinct mechanisms, such as mTOR activation by leptin signaling pathway 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Early Drosophila embryos also undergo a process of lipid droplet diffusion to aggregation and to spreading [ 71 ]. During cell mitosis, lipid droplets change from a dispersed state to a highly aggregated state [ 72 ]. As microtubules are remodeled in the cell during mitosis, lipid droplets may aggregate together because there are no microtubules to attach to.…”
Section: Effect Of Motility On the Distribution Of Lipid Droplets In Cellsmentioning
confidence: 99%
“…In animal embryos it is usually observed that there are large differences in the number of lipid droplets in daughter cells originating from the same fertilized egg. In NIH-3T3 cells, on the other hand, lipid droplets are extremely closely associated with the spindle during mitosis, and ultimately the distribution of lipid droplets between mother and daughter cells is homogeneous [ 72 ]. What regulates the distribution of lipid droplets between mother and daughter cells in mitosis and whether lipid droplet movement affects the distribution process still need further investigation.…”
Section: Questions In Lipid Droplet Motility Researchmentioning
confidence: 99%